Memenuhi keperluan pelajar di universiti awam Malaysia: Aspek pendapatan dan perbelanjaan - Abdullah, Siti Alida John (Universiti Utara Malaysia, 2007)
Persuing education at institutions of higher education today constitutes an economic, social and personal requirement.There are various advantages associated with investment for this purpose either by the individual student, family, or the society.However, the current higher education scenario requires not only the direct contributions from the government but students and their families too should also make direct contribution to the cost of higher education.Therefore, it is important for all parties to conscientiously review the sources of funding that can cover students’ requirements while they were at the institutions of higher education. Funding may come from various sources such as scholarships, subsidy or grants, loans from various sources, contributions from parents and families, income earned by the students who engaged in full-time or part-time jobs during their course of study, and also from students’ savings.In addition, there are various costs associated with higher education.Other than indirect costs such as the loss of students’ income during their study period, other direct costs normally borned by the students include tuition fees and living costs.Study findings from three public institutions of higher education showed differences among student groups not only in terms of the total expenditure but also from the priorities given to various categories of expenditure.